Religia i polityka. Taktyki oporu w rosyjskiej sztuce współczesnej - Zydorowicz, Jacek (Przegla̜d religioznawczy, 2022)
In the construction of the post-Soviet identity after perestroika, the authorities centralized in the Kremlin and the Orthodox Church turned out to be clearly active factors, which seemed to be supplemented by the oligarchies of the new financial elites. In the face of Putin’s aggression against Ukraine, the West reacted not only with sanctions, but also with the so-called cancel culture. That is why it is worth recalling the dissident activities of Russian artists and activists, and looking at their critical tactics and strategies, which target both the state authorities and the Orthodox Church.